PUTUSAN MAHKAMAH KONSTITUSI DALAM MEMUTUS PERKARA BERSIFAT ULTRA PETITA PERSPEKTIF SIYASAH SYAR’IYYAH - Harianto Harianto; Khairuddin Wahid; Etry Mike (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Abstract: Indonesia is a constitutional state so that in 2003 the Constitutional Court was born through Article 24 and Article 24 of the 1945 Constitution C. In its development in Indonesia the Constitutional Court has made many decisions decisions that contain ultra petita or who do not break with ultra petita. The existence of the decision of the Constitutional Court which contains ultra petita is a lot of debate so that the author tries to study and examine through the perspective of Fiqh Siyasah. Keywords: Constitutional Court; Ultra Petita; Verdict.